Bright Beginnings: Jewish Christian Relations in the Holy Land, AD 400-700 - Ribak, Eliya (Studies in Christian-Jewish Relations, 2011)
This paper is an archaeological analysis of the relationship between Jews and Christians in Byzantine Palestina, based on a catalogue of excavated Byzantine sites in the region. It suggests that different communities shared similar material cultures of religious practice, probably resulting from peaceful inter-communal interaction. These communities frequently occupied the same landscapes, and even the same settlements. This evidence is used to argue for closer and more peaceful co-existence between Jews and Christians in Byzantine Palestina than is usually supposed. It is suggested that this relative religious harmony contributed to the economic prosperity of the region in the Byzantine period and makes it a bright beginning for Jewish-Christian relations.